Long term impact of PositiveLinks: Clinic-deployed mobile technology to improve engagement with HIV care. - Chelsea E Canan; Marika E Waselewski; Ava Lena D Waldman; George Reynolds; Tabor E Flickinger; Wendy F Cohn; Karen Ingersoll; Rebecca Dillingham (PLoS ONE)
Background PositiveLinks (PL) is a smartphone-based platform designed in partnership with people living with HIV (PLWH) to improve engagement in care. PL provides daily medication reminders, check-ins about mood and stress, educational resources, a community message board, and an ability to message providers. The objective of this study was to evaluate the impact of up to 24 months of PL use on HIV viral suppression and engagement in care and to examine whether greater PL use was associated with improved outcomes. Setting This study occurred between September 2013 and March 2017 at a university-based Ryan White HIV clinic. Methods We assessed engagement in care and viral suppression from study baseline to the 6-, 12-, 18- and 24-month follow-up time periods and compared trends among high vs. low PL users. We compared time to viral suppression, proportion of days virally suppressed, and time to engagement in care in patients with high vs. low PL use. Results 127 patients enrolled in PL. Engagement in care and viral suppression improved significantly after 6 months of PL use and remained significantly improved after 24 months. Patients with high PL use were 2.09 (95% CI 0.64-6.88) times more likely to achieve viral suppression and 1.52 (95% CI 0.89-2.57) times more likely to become engaged in care compared to those with low PL use. Conclusion Mobile technology, such as PL, can improve engagement in care and clinical outcomes for PLWH. This study demonstrates long-term acceptability of PL over two years and provides evidence for long-term improvement in engagement in care and viral suppression associated with PL use.